Annual Development Plan of Madhya Pradesh 1958-59 - Planning Commission (Planning Commission, 1958)
Before describing the salient features of the Annual Development plan of Madhya Pradesh for the year 1958-59, it is necessary to have some idea of the new Madhya Pradesh which came into existence on 1st November 1906 and is comprised of the following regions:-(i) Mahakoshal, (ii) Madhya Bharat (minus Sunel Tappa of Mandsaur District). (iii) Vindhya Pradesh, (iv) Bhopal, and (v) Sironj Sub-Division of Rajasthan.
Government of Madhya Pradesh, Planning and Development Department